AB0914 EFFECT OF VITAMIN D SERUM CONCENTRATION ON ARTRALGIA INDUCED BY ADJUVANT THERAPHY WITH AROMATASE INIBITORS IN NON METASTATIC BREAST CANCERS SURVIOVORS. (June 2019) - Gotelli, Emanuele; Schenone, Carlotta; Cattelan, Francesco; Alessandri, Elisa; Goegan, Federica; Patanè, Massimo; Ghio, Massimo; Cutolo, Maurizio; Paolino, Sabrina
Abstract : Background: Hand arthralgia is often reported by breast cancer patients treated with adjuvant hormonal therapy. Aromatase inhibitors (AIs) improve survival in postmenopausal women with hormone-sensitive breast cancer, but can cause joint pain and stiffness (2). Low concentration of vitamin D in adults can cause musculoskeletal pain and joint discomfort (1). No data are available to date, on serum concentrations of (25-hydroxyvitamin D) [25 (OH) D3 ] vitamin D in AI-treated patients and possible relationship with arthralgia. Objectives: To evaluate possible correlation between different 25 (OH) D3 serum concentrations and hand arthralgia in patients with breast cancer treated with AIs. Methods: All patients that during the AIs therapy develop arthralgia referred to the rheumatologist; they reported the pain following the VAS (visual analogic scale) and contemporary performed a sample blood for dosage of vitamin D as well as biomarkers for inflammation and autoimmunity to exclude concomitant immune/inflammatory rheumatic musculoskeletal causes. Results: In a group of 63 women taking AIs (mean age 62.3±9.8years; disease duration from first assumption of AIS 10.6±3.2 months) 81% reported hand arthralgia and stiffness within the first year of follow-up; the most prevalent site of pain localization was bilateral hands (85%). Symptom was associated with minimal increase of serum parameters of inflammation (the mean value of C-reactive protein was 7.1±3.0 mg(L (normal value 0-5) but negative autoimmune profile (negative rheumatoid factors and anticitrullinated protein antibodies). The mean 25(OH)D3 serum concentration was 18.4± 8.5 ng/ml. Only 9% of women had an adequate (≥ 30 ng/ml) [25 (OH) D3 ] vitamin D serum levels, 70% were insufficient (> 10 < 20 ng/mL), and 21% were severely deficient (< 10 ng/mL). 55% of patients started AIs after chemotherapy. From the group that received AIs after chemotherapy 77% patients with arthralgia were found during the first years of hormonal therapy, in the group that previously did not take chemotherapy 88% of patients referred arthralgia. There was any difference on vitamin D serum levels between patients previously treated or not treated with chemotherapy (17.8± 7.8vs 19.3± 9.7 p=0.6). After subdivision of patients that referred hand arthralgia according to the different type of AIs used: 22% have been treated with tamoxifen, 30%, anastrozole and 48% letrozole. Therefore, the baseline serum vitamin D concentrations did not significantly predict arthralgia in the overall group (P = 0.70) or separately in the single AIs group (anastrozole (P = 0.60) or tamoxifene(P=0.30) or letrozole (P = 0.60, respectively). Conclusion: Vitamin D serum concentrations in women treated with AIs are at lowest ranges in the majority of the patients analysed, but no apparent interference with musculoskeletal symptoms was found related to the different concentrations; the cause of arthralgia might be better related to estrogen deficiency induced by AIs their self. References: [1] Kathryn R, et al. 2017 Ther Adv Musculoskelet Dis.9(6):131-135 [2] Hsieh KP, et al. 2014. PLoS One, 9, e87027. Disclosure of Interests: None declared